Penerapan Metode Istima’ untuk Meningkatkan Keterampilan Menyimak Bahasa Arab Siswa SDIT Bait Adzkia Islamic School Ciputat - Mutmainnah; Nururahmah, Nola; Haqi, Ahmad Shaubil; Rifa'i, Muhammad; Alawiyah, Lalah (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2025)
This study explores the implementation of the istimā’ (listening) method in Arabic language instruction at the integrated Islamic elementary school level. The purpose of this research is to describe the istimā’ learning strategies, analyze the media and approaches used, and explain their contribution to improving students’ Arabic listening skills at SDIT Bait Adzkia Islamic School Ciputat. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that the istimā’ method—applied through Arabic songs, simple dialogues, audiovisual media, and interaction with native speakers—significantly enhances students’ listening abilities. Instructional strategies are adapted to students who have not yet mastered Arabic script, such as the use of Latin transcription and reinforcement through tahfidz (memorization). Students demonstrated positive responses, vocabulary improvement, and better understanding of basic Arabic expressions. This study serves as a valuable reference for developing istimā’-based instructional methods in integrated Islamic schools facing similar challenges in Arabic literacy and language exposure.